Late Pleistocene-Holocene events on the continental slope of the Laptev Sea: Evidence from benthic and planktonic foraminiferal assemblages - Ovsepyan, Ya. S.; Taldenkova, E. E.; Bauch, Henning A.; Kandiano, Evgeniya S. (Stratigraphy and Geological Correlation, 2015)
This work is dedicated to the study of benthic and planktonic foraminifers and is a contribution to the multidisciplinary investigations of Core PS51/154-11 from the Laptev Sea. The paleoecological analysis of foraminiferal assemblages makes it possible to reconstruct in detail environmental changes on the western continental margin of the Laptev Sea during the Late Pleistocene and Holocene. The examined core dated by the AMS radiocarbon method is divided into intervals that reflect main stages in the regional evolution for the last 17.6 k.y.: early deglaciation, Bølling–Allerød warming, Younger Dryas cooling, transition to the Interglacial, Holocene climatic optimum, Middle-Late Holocene. The presence of subpolar planktonic foraminifers and benthic species Cassidulina neoteretis (Tappan) provides grounds to reconstruct for the continental slope area stages of the enhanced activity of subsurface Atlantic-derived water in the intervals of 12.0–14.7 and 0.6–5.4 ka. The benthic assemblage reflects changes in depositional environments related to the postglacial transgression and also climatic change impacts affecting bioproductivity. The events defined on the basis of foraminifers are correlated with climatic oscillations and changes in circulation of water masses.